Potentially inappropriate medication prescribing among elderly patients with cardiovascular diseases - Stojanović Goran; Đurić Dušan; Jakovljević Biljana; Turnić-Nikolić Tamara; Maričić Milena; Stojanović Svetlana; Milovanović Olivera (Vojnosanitetski Pregled)
Background/Aim. The growing number of older adults means higher medicine utilization. The aim of the study was to determine the frequency and identify risk factors of potentially inappropriate medication (PIM) in the elderly population with cardiovascular diseases. Methods. The retrospective, cross-sectional study was performed in 2018, and the relevant data were collected during the period from January 2016 to December 2017. The study sample included 1,500 patients over 65 years with cardiovascular disease who had medical records at the Institute for Gerontology and Palliative Care, Belgrade. Assessment of PIM was done by standard international criteria such as the American Geriatrics Society 2015 updated Beers Criteria for PIM use in older adults. Results. PIM frequency in the elderly population was 70.3%. In relation to gender, it was more frequent in female elders. The mean number of prescribed drugs was similar for 2016 and 2017, 7.2 and 7.3, respectively. The most common were: medium-acting benzodiazepines (70.9%), central α blockers (23.98%), and antipsychotics (typical and atypical) (20.94%). The most common comorbidity was noted in a group labeled with the International Disease Classification I00-I99, which includes heart and blood vessel diseases [n = 2,658 (36.9%)]. The most common diagnoses belonged to the subgroups I10-I15 [hypertensive diseases, n = 1,298 (18%)], I20-I25 [ischemic heart diseases n = 542 (7.5%)], I30-I52 [other forms of heart disease, n = 705 (9.8%)], I60-I69 [cerebrovascular diseases, n = 94 (1.3%)], and I80- I89 [diseases of veins, lymph vessels, and lymph nodes n = 12 (0.17%)]. The risk factors for PIM were: polypharmacy, gender, nicotine use, cognitive status, nutrition state, and the number of diseases registered in the study sample. Conclusion. Cardiovascular diseases in the elderly population are associated with a high prevalence of PIM. Creating health recommendations for prescribing drugs to the elderly that would emphasize these factors could reduce the prevalence of PIM in this population.